Efficacy of Tacrolimus in Uveitis, and the Usefulness of Serum Tacrolimus Levels in Predicting Disease Control. Results from a Single Large Center. (17th November 2022) - Luis, Joshua; Alsaedi, Abdulrahman; Phatak, Sumita; Kapoor, Bharat; Rees, Angela; Westcott, Mark
ABSTRACT: Aims: To evaluate the efficacy of tacrolimus in patients with noninfectious uveitis, as well as the usefulness of serum tacrolimus concentration measurements in predicting disease control. Methods: A retrospective review was carried out on 71 eligible patients from a single specialist uveitis center for minimum 1-year follow-up. Analysis was carried out on disease activity, visual acuity, and trough serum tacrolimus concentrations (STC). Results: At 1-year follow-up, disease control was achieved in 49 patients (69.0%), this was significantly more likely in patients with trough STC levels above 5 ng/mL (88% vs 53%, p = .002). There was a significant reduction in oral prednisolone (dose ≥7.5 mg, 86% vs 54%, p < .0001). Tacrolimus was discontinued in 12 patients (17%) due to side effects. Discussion: In this study cohort, oral tacrolimus was effective and well tolerated in the treatment of noninfectious uveitis. Trough STC between 5 ng/mL and 10 ng/ml was associated with better disease control at 1-year follow-up.